2014
DOI: 10.1039/c4nr00500g
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level control of conductive nano-filament evolution in HfO2 ReRAM by pulse-train operations

Abstract: Precise electrical manipulation of nanoscale defects such as vacancy nano-filaments is highly desired for the multi-level control of ReRAM. In this paper we present a systematic investigation on the pulse-train operation scheme for reliable multi-level control of conductive filament evolution. By applying the pulse-train scheme to a 3 bit per cell HfO2 ReRAM, the relative standard deviations of resistance levels are improved up to 80% compared to the single-pulse scheme. The observed exponential relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 32 publications
2
91
0
Order By: Relevance
“…The memristive switching from high-resistance state to low-resistance state could be attributed to CF formation at the grain boundaries containing a high concentration of oxygen vacancies 33 . On the other hand, electric field could play an important role in switching from low-resistance state to high-resistance state 34 . It was suggested that electrical pulses lead to a progressive narrowing of the CF, and finally a gap is formed and the memristor switches to the high-resistance state 33,34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The memristive switching from high-resistance state to low-resistance state could be attributed to CF formation at the grain boundaries containing a high concentration of oxygen vacancies 33 . On the other hand, electric field could play an important role in switching from low-resistance state to high-resistance state 34 . It was suggested that electrical pulses lead to a progressive narrowing of the CF, and finally a gap is formed and the memristor switches to the high-resistance state 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, electric field could play an important role in switching from low-resistance state to high-resistance state 34 . It was suggested that electrical pulses lead to a progressive narrowing of the CF, and finally a gap is formed and the memristor switches to the high-resistance state 33,34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main concept underlying the multi-level cell (MLC) operation of RRAM is the tunability of the filament geometry by changing the maximum power dissipation through the device during the SET and RESET processes. Zhao et al [26] have noted that MLC operation can be used for synaptic weights by programming the device with different pulse amplitudes. This causes the device to latch onto different levels of resistance as it is undergoing the RESET transition.…”
Section: B Rram Synapse: Multi-level Cell Operationmentioning
confidence: 99%
“…The bipolar VCM-type resistive switching relates to a redistribution of oxygen vacancies in the switching filament [1]. Whereas theoretical models predict a gradual reset behavior for VCMtype switching TMOs [2,3], in experiments different reset phenomena are reported: abrupt [4] and gradual, whereas the latter is interesting for neuromorphic applications [5,6]. In addition, the measured switching behaviors often deviate from the universal switching rule [7,8] predicting that for a system with linear I(V)-characteristic in the LRS, the voltages of set and reset should be symmetric and the LRS should scale with the current compliance during set.…”
Section: Introductionmentioning
confidence: 96%